Business solution for a food service company based on a modern nutrition concept (case of Russia) - Tarasov, Stanislav; Campbell, Jan, 1946-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
Increasing level of public concerns about ageing and obesity problems accompanied by the advent of more and more health conscious consumers have put a priority on the health and wellness industry development which has started transformation from a niche category towards the mainstream. As a human being is an individual with unique known characteristics (like age, gender, health state, lifestyle) and less known characteristics like a genetic predisposition, the nutrition plan should be designed around these characteristics. Being aware of genetic predisposition of an individual allows to develop the appropriate health strategy for the particular individual. A systematization of these individual programs would support the development of a new generation of health practitioners. Russia is experiencing serious demographic problems with decreasing population and low life expectancy; high mortality rate from heart diseases and quite high obesity rates. It is expected that nutrigenomics concepts can be successfully developed in Russia due to its solid scientific base, relatively high level of medicine and the ever increasing awareness of the need for a healthy quality life especially within young generation. The goal of the thesis therefore is to analyze the key trends in the global and Russian food industries and develop a business idea of commercializing the personalized nutrition concept in the Russian food service market.
Vedoucí práce: Jan Campbell
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses